Comparative polypharmacokinetics of nine anti-inflammatory components of Jinyinhua (Lonicerae Japonicae Flos) and Shanyinhua (Lonicerae Flos) in mice with p-xylene-induced ear edema - L.I. Haiying; X.I.A.O. Meifeng; P.A.N. Xue; L.I. Wenjiao; Z.H.O.U. Yiqun; L.I.U. Wenlong; H.E. Fuyuan (Digital Chinese Medicine, 2023)
Objective: To reveal the integral in vivo polypharmacokinetics (PPK) similarity or difference between Jinyinhua (Lonicerae Japonicae Flos, LJF) and Shanyinhua (Lonicerae Flos, LF), and provide reference for their clinical application. Methods: The PPK model and its total quantum statistical moment similarity (TQSMS) method were used to compare the integral PPK profiles of nine components with anti-inflammatory efficacy (rutin, caffeic acid, chlorogenic acid, cryptochlorogenic acid, dispsacoside B, macranthoidin B, isochlorogenic acid A, isochlorogenic acid B, and isochlorogenic acid C) of LJF and LF. A total of 54 Specific Pathogen Free (SPF) grade Kunming (KM) mice were randomized into LJF group and LF group (n = 27), and each group was divided into nine subgroups (n = 3) according to different time points. Subsequently, mice model of p-xylene-induced ear edema was constructed by oral administration of LJF and LF. The concentrations of the nine anti-inflammatory components in plasma samples of the mice were determined by ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS/MS). And the pharmacokinetics (PK) parameters of single component and the integral PPK parameters [total quantum statistical moment (TQSM) and TQSMS] of multiple components were calculated by Drug And Statistics (DAS) software and home-brew programs with Excel, respectively. Results: There were significant differences in single-component PK parameters between LJF and LF (P < 0.05). Whereas, no significant differences were found in multi-component TQSM parameters, including total quantum zero moment (AUCT0-t, AUCT0-∞) and total quantum first moment (MRTT0-t, MRTT0-∞) for the total quanta (P > 0.05). Accordingly, single-component TQSMS varied from 0.220 4 to 0.968 9, and that for the total quanta was 0.828 4, suggesting no significant differences in the speed and extent of bioavailability between LJF and LF. Furthermore, in light of high TQSMS (0.828 4), the integral PPK profiles of the nine anti-inflammatory components of LJF and LF were similar under 90% confidence intervals. Conclusion: The PPK model and its TQSMS method are appropriate and efficient to compare the similarity or difference of integral PPK profiles of multi-component herbal medicines. It is suggested in this research that LJF can be replaced with LF or vice versa for anti-inflammatory treatment.